Juridical Review: Basis for Making a Land Sale Deed by a Notary in the Correlation of Land Administration Issues - Sudjono, Ira (Lafadz Jaya Publisher, 2024)
This research aims to describe the Juridical Review: Basics for Making Land Sale Deeds by Notaries in the Correlation of Land Administration Issues. In this research, the normative legal research method is one where the study is based on legal materials from literature. The research specifications used are analytical descriptive. The legal material collection technique used in this research is a documentation technique which is carried out by inventorying and categorizing legal materials such as statutory regulations, literature, and other legal materials. The data analysis method used is qualitative analysis, namely data obtained directly according to facts in the field. The results of PPJB's research are the initial agreement made by the seller and buyer as an initial binding before the AJB is made before the PPAT. The basis for making the PPJB by the parties is that the new APPJB is an agreement because not all payments have been made, APPJB where the payment has been made in full, but the AJB cannot be made before the PPAT, because the sale and purchase process has not been completed, for example: The certificate is still in the process of certificate splitting, and in the process of merging as well as various other reasons why AJB cannot be created.